THE ECONOMIC IMPACT OF TECHNOLOGY ON THE TRANSFORMATION OF ISLAMIC EDUCATION - Harris, Taufiq; Wahyudi, M Furqon; Maftuh, Maftuh (Fakultas Ekonomi dan Bisnis Islam Universitas Al- Hikmah Indonesia - Jurnal Ekonomi Pengabdian Masyarakat, 2024)
The aim of community service is to provide a detailed and in-depth explanation of the role of technology in the transformation of Islamic education. The community service is conducted through seminars, utilizing lecture methods and discussion methods. The expected outcome is for participants to be able to utilize technological tools to achieve higher quality Islamic education. The use of technology in Islamic education emphasizes Islamic values and four important factors that must be integrated into the curriculum. 1) Religion and Character Building, making religion and character the foundation of strong spiritual and moral values. 2) Smart, developing critical and analytical thinking through the use of technology. 3) Science, expanding insights and understanding of various scientific disciplines. 4) Life Skill, equipping practical skills relevant to the needs of the times, so that the use of technological tools in the transformation of Islamic education aligns with the goals of national education.